Harnessing Microbial Innovations for a Viksit Bharat: Bridging Research to Societal Impact (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
development. Microorganisms possess diverse metabolic capabilities that allow them to contribute to healthcare, agriculture, environmental sustainability, and industrial biotechnology. Recent advancements in molecular microbiology, genomics, and microbial biotechnology have enabled the development of innovative tools such as rapid molecular diagnostics, microbial biofertilizers, bioremediation technologies, and bio-based industrial production systems. These innovations have significant potential to address major societal challenges, including infectious diseases, environmental pollution, and food insecurity.India’s national development vision under Viksit Bharat 2047 emphasizes technological innovation, scientific advancement, and sustainable economic growth. Microbial technologies can play a crucial role in achieving these objectives by strengthening healthcare systems, improving agricultural productivity, and promoting environmentally sustainable industrial processes. For instance, microbial biotechnology has been widely applied in biofertilizers, wastewater treatment, and pollution remediation, demonstrating its capacity to support ecological sustainability and resource conservation.Despite significant progress in microbiological research, the translation of scientific discoveries into practical societal applications remains limited due to technological, financial, and policy-related barriers. Bridging this gap requires interdisciplinary collaboration among researchers, policymakers, and industry stakeholders. This study examines the potential of microbial innovations to contribute to sustainable development and national growth. The findings highlight the importance of investment in biotechnology research, innovation-driven policy frameworks, and effective knowledge transfer systems to ensure that microbial research delivers tangible benefits for society.